A Comparison of Three-Layer and Single-Layer Small Vascular Grafts Manufactured via the Roto-Evaporation Method - Zumbardo Bacelis, Gualberto Antonio (2024)
This study used the roto-evaporation technique to engineer a 6 mm three-layer polyurethane vascular graft (TVG) that mimics the architecture of human coronary artery native vessels. Two segmented polyurethanes were synthesized using lysine (SPUUK) and ascorbic acid (SPUAA), and the resulting materials were used to create the intima and adventitia layers, respectively. In contrast, the media layer of the TVG was composed of a commercially available polyurethane, Pearlbond 703 EXP. For comparison purposes, single-layer vascular grafts (SVGs) from individual polyurethanes and a polyurethane blend (MVG) were made and tested similarly and evaluated according to the ISO 7198 standard. The TVG exhibited the highest circumferential tensile strength and longitudinal forces compared to single-layer vascular grafts of lower thicknesses made from the same polyurethanes. The TVG also showed higher suture and burst strength values than native vessels. The TVG withstood up to 2087 ± 139 mmHg and exhibited a compliance of 0.15 ± 0.1%/100 mmHg, while SPUUK SVGs showed a compliance of 5.21 ± 1.29%/100 mmHg, akin to coronary arteries but superior to the saphenous vein. An indirect cytocompatibility test using the MDA-MB-231 cell line showed 90 to 100% viability for all polyurethanes, surpassing the minimum 70% threshold needed for biomaterials deemed cytocompatibility. Despite the non-cytotoxic nature of the polyurethane extracts when grown directly on the surface, they displayed poor fibroblast adhesion, except for SPUUK. All vascular grafts showed hemolysis values under the permissible limit of 5% and longer coagulation times.